STEPPING SUCCESS OF WOMEN ENTREPRENEURS IN INDIA - A STUDY - R.Praiya, (International Journal of Psychosocial Rehabilitation, 2020)
Women in India are amount to 48% of the total population. Their participation in economic growth is 38% only. Women entrepreneur in the world is 25% to 33% according to the World Bank report. To achieve socially balanced economic development, role of women entrepreneurs in developing countries are vital. Their participation will develop multi-dimensional growth and benefit in economy. After 1947, there is a continuous increase in self-employed women in India. Women registered enterprises were only 2.15 lakh of 15.64 lakh enterprises in India, according to the Fourth All India Census of MSME in 2007. But according to the World Bank report in 2015 there were 2.69 million women unregistered MSME in India. There are 8.05 million women entrepreneurs in India according to the sixth Economic census. Technology facility, network availability and worldwide communication open path to women entrepreneur both online and offline digital world. Digital media increases market tactics and reaches Women entrepreneur’s innovative ideas in nook and corner. This study attempts to understand nature of Women entrepreneurs, their challenges and their stepping success in digital world.